Odontoid parameters in subjects with and without degenerative cervical spondylosis - Kang, Tao; Chen, Weiyou; Huang, Longao; Xu, Hongyuan; Jiang, Hua (BMC musculoskeletal disorders, 2025)
This study aimed to explore radiographic differences in odontoid parameters between subjects with and without degenerative cervical spondylosis (DCS). Lateral cervical X-rays and magnetic resonance imaging (MRI) from 51 healthy subjects (control group) and 107 DCS patients (case group) were retrospectively reviewed. The odontoid parameters including odontoid incidence (OI), odontoid tilt (OT), and related cervical sagittal parameters were measured: C2 slope (C2S), C0-2 angle (C0-2), C2-7 angle (cervical lordosis [CL]), T1 slope (T1S), and T1S minus cervical lordosis (T1S - CL). An independent-samples t test and the Wilcoxon rank-sum test were used to compare these parameters between the two groups. Spearman's correlation analysis assessed the correlations among these parameters. The formula CL = 0.36 × OI - 0.67 × OT - 0.69 × T1S was used to predict CL and confirm its efficacy. The OI and OT were 15.67° ± 4.41° and 9.42° ± 4.66° in healthy subjects and 18.84° ± 3.41° and 4.47° ± 5.93° in DCS patients, with significant differences observed between the two groups (p < 0.001). In healthy subjects and DCS patients, OI and OT were correlated with C2S, C0-2, C2-7, and T1S - CL. The formula for predicting CL had predictive efficacy in healthy subjects (R = 0.88) and patients with DCS (R = 0.64). OI and OT serve as valuable supplements to the established parameters for evaluating and predicting normal cervical lordosis, aiding in assessing cervical spine balance and guiding therapeutic strategies to restore it.